The Silent Struggle: Exploring the Link between Xenoglossophobia and Adult Self-Esteem, Quality of Life, and Communication Experiences - Abbas, Salbia; Latif, Muhammad; Anjum, Razia (Annals of Human and Social Sciences, 2023)
The latest research delved into the relationship between Xenoglossophobia and self-esteem, quality of life, and communication experiences in adults. Empirical finding is a cross-sectional study based on quantitative approach. Data was collected through the application of three measurement scales “Foreign language classroom anxiety Scale (FLCAS), Rosenberg self-esteem scale (RSE) and quality of life scale (QOLS) along with self-developed demographic sheet. Sample was comprised of 400 participants recruited through convenience sampling technique. Both descriptive and inferential statistics were used for the analysis of the data with the application of SPSS (.22). Results of regression analysis explored that there is a negative correlation between Second language anxiety and self-esteem (r = -.308, P < 0.01). While a significant positive relationship exists between SLA and quality of life (r = .417, P < 0.01). Conclusively, it is stated that as three constructs are associated with each other. This research indicates that there is non-significant relationship between Xenoglossophobia and quality of life while there is a significant relationship between Xenoglossophobia and self-esteem.